Instrumental Tracheal Rupture - S. A. Khachatryan; F. A. Chernousov; Sh. N. Danielyan (Неотложная медицинская помощь)
Abstract Tracheal rupture is an urgent life-threatening complication that relates to complex and poorly understood areas of trauma surgery. The article presents a review of modern world and domestic literature on instrumental tracheal ruptures, the Relevance of early diagnosis and various treatment methods. Based on an analysis of modern literature data, the article describes the issues of conservative and surgical treatment methods, as well as an assessment of their results. The problem of the diagnostic algorithm and the choice of conservative, surgical treatment has not been solved and remains relevant. The issues of treating patients with a defect in the membranous wall of the trachea in intensive care and in need of artificial ventilation in clinical practice remain unresolved. All of the above indicates the Relevance of the study.Aim of the study To present data from domestic and foreign literature on the diagnosis and treatment of instrumental tracheal ruptures.Material and methods A review of the literature was carried out for the period from 1993 to 2024 in Russian and English, available on the databases Pubmed, Medline, UpTodate, Scopus, E-library, on topics such as post-intubation tracheal rupture, iatrogenic tracheal rupture, diagnosis and treatment of instrumental tracheal ruptures, closed tracheal injury.Results The concept of the classification system, risk factors, etiopathogenesis is outlined. Information is provided on the diagnostic significance of computed tomography and tracheobronchoscopy. Close attention is paid to the methods and choice of treatment tactics, the principles of intraoperative tactics, and the strategy of conservative treatment. A comparative assessment of treatment Results and their complications with a conservative or surgical treatment approach is given.Conclusion Thus, an analysis of domestic and foreign literature indicates that the issues of diagnosis and treatment of iatrogenic tracheal injuries remain largely unresolved. There is no generally accepted algorithm for instrumental diagnosis of tracheal ruptures. There are no uniform approaches to determining indications and contraindications for conservative and surgical treatment of tracheal injuries. There are diametrically opposed opinions regarding the choice of treatment tactics. These contradictions create significant difficulties in assessing the Results of treatment of this complex category of patients.